If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X-2(13+7X)=11
We move all terms to the left:
X-2(13+7X)-(11)=0
We add all the numbers together, and all the variables
X-2(7X+13)-11=0
We multiply parentheses
X-14X-26-11=0
We add all the numbers together, and all the variables
-13X-37=0
We move all terms containing X to the left, all other terms to the right
-13X=37
X=37/-13
X=-2+11/13
| 2(10x-4)=3(2x+16) | | x*(-12+18)=40 | | 6m+100=40 | | X^2-6x-9+(x-3)(x+4)=0 | | t+24t=12 | | x2+8x+10=30 | | -5-2.5x-19=-4 | | 4(0.75x-3)=18 | | 3+4.5+0.5x=12 | | x+16=3x.x= | | (5x)+(3x+2)+90=180 | | (-17/19x)+51=0 | | 9m+18-4m=-5 | | 20y+8=7-14y | | 9x+4=4x-3 | | x*1.57=x+100 | | x*1.55=x+100 | | 18b+2+6b=20b+10 | | (k+27)^3=159 | | 0.24*g=9.6 | | 6x^2+13x+97=0 | | (p-4)(p+1)=0 | | 3/5x-1/3=0 | | 2(x-7)^2=10 | | 16/4+2a=18 | | (x-2)(x-3)=13 | | -12(3x-6)=-108 | | 9x-10x/12=3 | | 6(3x+6)=87 | | 2y+30=2(50)+30=130 | | 3b/4+b=14 | | 6(r-2)=24 |